CMMSE on explicit and numerical solutions for stochastic PDEs: Fisher and Burgers equations. Issue 3 (6th May 2020) - Suazo, Erwin; Oraby, Tamer; Palacio, Jose
Abstract: In this work we study a stochastic susceptible‐infected (SI) model with space‐uniform white noise. We present conditions to find exact solutions and numerical simulations are compared to these exact solutions in some cases. We demonstrate that the model is exponentially asymptotically stable almost surely. We show the global stability and local stability of a special case of the model.